Reflexive Translation Studies Translation as Critical Reflection - Kadiu, Silvia (UCL Press, 2019)
In the past decades, translation studies have increasingly focused on the ethical dimension of translational activity, with an emphasis on reflexivity to assert the role of the researcher in highlighting issues of visibility, creativity and ethics. In Reflexive Translation Studies, Silvia Kadiu investigates the viability of theories that seek to empower translation by making visible its transformative dimension; for example, by championing the visibility of the translating subject, the translator's right to creativity, the supremacy of human translation or an autonomous study of translation. Inspired by Derrida's deconstructive thinking, Kadiu presents practical ways of challenging theories that argue reflexivity is the only way of developing an ethical translation. She questions the capacity of reflexivity to counteract the power relations at play in translation (between minor and dominant languages, for example) and problematises affirmative claims about (self-)knowledge by using translation itself as a process of critical reflection.